Study of the effect of the peptide loading and solvent system in SPPS by HRMAS-NMR - Valente, A. P.; Almeida, FCL; Nakaie, C. R.; Schreier, S.; Crusca, E.; Cilli, Eduardo Maffud [UNESP] (Wiley-Blackwell, 2005)
The SPPS methodology has continuously been investigated as a valuable model to monitor the solvation properties of polymeric materials. In this connection, the present work applied HRMAS-NMR spectroscopy to examine the dynamics of an aggregating peptide sequence attached to a resin core with varying peptide loading (up to 80%) and solvent system. Low and high substituted BHAR were used for assembling the VQAAIDYING sequence and some of its minor fragments. The HRMAS-NMR results were in agreement with the swelling of each resin, i.e. there was an improved resolution of resonance peaks in the better solvated conditions. Moreover, the peptide loading and the attached peptide sequence also affected the spectra. Strong peptide chain aggregation was observed mainly in highly peptide loaded resins when solvated in CDCl3. Conversely, due to the better swelling of these highly loaded resins in DMSO, improved NMR spectra were acquired in this polar aprotic solvent, thus enabling the detection of relevant sequence-dependent conformational alterations. The more prominent aggregation was displayed by the VQAAIDYING segment and not by any of its intermediary fragments and these findings were also corroborated by EPR studies of these peptide-resins labelled properly with an amino acid-type spin probe. Copyright (c) 2005 European Peptide Society and John Wiley & Sons, Ltd.
Keywords: NMR; high-resolution magic angle spinning; solid-phase synthesis; resin; peptide